Implementation of Village Government in Realizing Village Independence in the Tanimbar Islands Regency - Herpie LAMBIOMBIR; Tri HAYATI; Harsanto NURSADI; Dian.P.N. SIMATUPANG (Indonesia Strategic Sustainability, 2022)
Villages or other names have existed before Indonesia was formed. The existence of these regions is highly respected by the Republic of Indonesia and all of its regulations will serve as a reminder of the rights of the origin of the region. This research aims to analyzes Implementation of village government in realizing village independence. the research method used in this research is normative legal research. Implementation of the Village Law on the implementation of village government in Tanimbar Islands Regency has encouraged every village device to carry out its main duties in accordance with good governance, transparent and accountable, and has succeeded in increasing the village status index where no longer found villages are very left behind and most have become developed and independent villages.